2018
DOI: 10.5539/jas.v10n11p29
|View full text |Cite
|
Sign up to set email alerts
|

Litter Dynamics in Eucalyptus and Native Forest in the Brazilian Cerrado

Abstract: The aim of this study was to evaluate the litter dynamics in the seasons of the year in three areas: Forest formation Cerradão (CE), and in two hybrids stands of Eucalyptus urophylla × E. grandis with different ages: E1 (34-58 months) and E2 (58-82 months). The produced litter, stored litter and the remaining mass was collected over 720 days. The evaluation of the remaining litter mass in each area was performed from the random distribution of 648 litter bags on the soil. Chemical analyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
2
14
0
5
Order By: Relevance
“…We observed that litter decomposition presented a strong seasonal trend, occurring more intensively in the rainy season. This pattern corroborates studies reporting that litter decay can be three to seven times faster in rainy than in dry seasons (Peña-Peña and Irmler, 2016;Ribeiro et al, 2018).…”
Section: Litter Decay Relates To Soil Epigeic Fauna and Chemistrysupporting
confidence: 91%
“…We observed that litter decomposition presented a strong seasonal trend, occurring more intensively in the rainy season. This pattern corroborates studies reporting that litter decay can be three to seven times faster in rainy than in dry seasons (Peña-Peña and Irmler, 2016;Ribeiro et al, 2018).…”
Section: Litter Decay Relates To Soil Epigeic Fauna and Chemistrysupporting
confidence: 91%
“…The k values were higher compared to a study conducted by Souza et al (2016) in a Dense Cerrado, in which the authors reported a coefficient of 0.0007. On the other hand, the k values were lower compared to Ribeiro et al (2018), in Cerradão with a coefficient of 0.0021. In the present study, the results showed that CD and DC are efficient in assimilating and decomposing the carbon material deposited on the soil.…”
Section: Leaf Decaymentioning
confidence: 79%
“…Comparing the biomass decay in percentage Ribeiro et al (2018) found a loss of 54% litter in a Cerradão, in the Distrito Federal, Brazil, and Souza et al (2016) found a loss of 30% in a Dense Cerrado, also in the Distrito Federal. Both studies reported the trend of decay verified in the present study, where CD had more biomass loss than DC.…”
Section: Leaf Decaymentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly to us, also found higher litter biomass for Eucalyptus plantations (11.71 Mg.ha -1 ) compared to native cerradão (9.18 Mg.ha -1 ). Ribeiro et al (2018) explain the higher litter biomass and litter C stocks in Eucalyptus plantations compared to native Cerrado (cerradão physiognomy) due to greater deposition and low decomposition rates of the plant material, as litter decomposition showed to be faster in the native Cerrado than in areas converted to Eucalyptus plantations. In our research, litter increase did not result on labile C gains; MBCS was substantially reduced, as the PMN, and the lowest NH4-N stocks were found in Eucalyptus plantations, what indicates poor litter quality.…”
Section: Discussionmentioning
confidence: 97%